Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan Melalui Motivasi Sebagai Variabel Intervening Pada Perumda Tirta Kanjuruhan Kabupaten Malang - Muhammad Faiz Labay Al Anshory (Lembaga Pengembangan Kinerja Dosen, 2024)
Companies can invest time and resources in developing, motivating, and nurturing the well-being of their employees. This not only has an impact on short-term success, but also on the company's long-term growth and sustainability. The purpose of this study is to analyze the Influence of Work Discipline on Employee Performance with Work Motivation as an Intervening Variable in Perumda Tirta Kanjuruhan, Malang Regency. The method used is quantitative in the form of explanatory research. The data was collected with a questionnaire that was distributed to all staff at Perumda Tirta Kanjuruhan, Malang Regency, totaling 80 people. Meanwhile, the data analysis used is SEM with PLS as the analysis technique. The results of the study showed that work discipline had an effect on employee performance at Perumda Tirta Kanjuruhan, Malang Regency. Work discipline affects work motivation at Perumda Tirta Kanjuruhan Malang Regency. Work motivation affects employee performance at Perumda Tirta Kanjuruhan, Malang Regency. Work discipline affects employee performance through work motivation at Perumda Tirta Kanjuruhan, Malang Regency. The conclusion in this study is that work discipline includes punctuality, precision, and consistency in carrying out tasks. Meanwhile, work motivation is a key factor that encourages employees to achieve their goals and give their best performance.